2007
DOI: 10.1111/j.1365-2672.2006.03224.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella Senftenberg strain W 775 during composting of biowastes and garden wastes

Abstract: Aims:  Determination of the minimum requirements (time–temperature relationship and moisture content) that are needed for a sufficient eradication of an indicator organism. Methods and Results:  To determine the hygienic safety of composting processes, the indicator organism Salmonella enterica ssp. enterica serotype Senftenberg strain W 775 (further abbreviated as W 775) was artificially inoculated on a meat carrier and monitored subsequently. Different types of composting processes, e.g. composting in enclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Hassen et al (36) also reported complete reduction of Salmonella species in composting of municipal waste once the temperature reached 55°C. Salmonella enterica serovar Senftenberg strain W775 was inactivated within 10 h of composting at 60°C, with a moisture content of 60 to 65% (37). Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hassen et al (36) also reported complete reduction of Salmonella species in composting of municipal waste once the temperature reached 55°C. Salmonella enterica serovar Senftenberg strain W775 was inactivated within 10 h of composting at 60°C, with a moisture content of 60 to 65% (37). Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ceustermans et al (3) demonstrated that Salmonella enterica serovar Senftenberg strain W 775 was inactivated within 10 h of composting at 60°C with moisture varying between 60 and 65%; however, when the moisture content of the compost was reduced by 5%, the survival rate was increased by 0.50 log/h. The moisture content of the compost mixture affects temperature distribution within the compost heap (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced feed ban has prompted renderers to impose fees for SRM disposal and consequently there is a desire to develop economical on-farm disposal methods for SRM. One economically feasible option may be composting as this has been shown to reduce pathogens (Van Herk et al 2004;Xu et al 2009) while producing a valuable fertilizer for agriculture crops (Ros et al 2006;Ceustermans et al 2007).…”
Section: Introductionmentioning
confidence: 99%